"Naked" Iridium(IV) Oxide Nanoparticles as Expedient and Robust Catalysts for Hydrogenation of Nitrogen Heterocycles: Remarkable Vicinal Substitution Effect and Recyclability. Issue 6 (18th January 2017) - Ji, Yi‐Gang; Wei, Kai; Liu, Teng; Wu, Lei; Zhang, Wei‐Hua
Abstract: Iridium(IV) oxide nanoparticles were facilely prepared from iridium trichloride hydrate and sodium hydroxide by a ball‐milling reaction at room temperature. The "naked" iridium nanocatalyst showed high stability and activity for the hydrogenation of a series of nitrogen heterocycles, for the first time, under a hydrogen balloon at room temperature with a selectivity of higher than 99%. Besides, an unprecedented substitution‐dependent effect was discovered, where substrates with vicinal substituents on 2‐, 3‐, or 8‐positions exhibited distinctly higher reaction rates than unsubstituted or remote substituted ones. Extraordinary recyclability was discovered in the hydrogenation of 2‐methylquinoline for 30 runs without loss of activity. Abstract :